Kid Owner - Green, Tim 1963- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2015)
"When Ryan learns his estranged father left him the Dallas Cowboys in his will, it is all Ryan can do to keep his dad's other son from snatching the team away"--
Keywords: Dallas Cowboys (Football team) -- Juvenile fiction; Dallas Cowboys (Football team) -- Fiction; Fathers and sons -- Juvenile fiction; Inheritance and succession -- Juvenile fiction; Stepbrothers -- Juvenile fiction; Football stories; Fathers and sons -- Fiction; Inheritance and succession -- Fiction; Stepbrothers -- Fiction; Brothers and sisters -- Fiction; Football -- Fiction; JUVENILE FICTION / Sports & Recreation / Baseball & Softball; JUVENILE FICTION / Family / Stepfamilies; JUVENILE FICTION / Business, Careers, Occupations